SOCIAL CONFLICT IN CUSTOMS AND VALUES: A CONTENT ANALYSIS OF INDONESIAN JUNIOR HIGH SCHOOL ENGLISH TEXTBOOKS - Alamsyah, Ajar; Sri Ardiasih, Lidwina; Puspitasari, Maya (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
The background of this research is the assumption that a gap exists, causing cultural conflict represented by Customs and Values (Culture) in English textbooks used in Junior High Schools, especially in grade 7. Therefore, the purpose of this research is to determine whether the gap is indeed true. Moreover, it will also be clear why the gap occurs and what the solution to the problem is. The research method employed is a qualitative approach using a content analysis research instrument to analyse the visualisations contained in English textbooks for grade 7 students in Junior High School. The visualisations are obtained from two selected English textbooks, namely English for Nusantara and English in Mind. The results of the study revealed social conflict in English textbooks used by 7th-grade junior high school students in the Customs and Values entity, which is part of the Culture sector. Based on a comprehensive data analysis, this study provides several conclusions. Referring to Berelson's content analysis steps, there was social conflict in terms of customs and values ​​in both English textbooks, namely English for Nusantara and English in Mind. After comparison, social conflict related to customs occurred more frequently than others, with a percentage of around 70% to 30%. Therefore, social conflict arose in both customs and values. This study contributes to the discourse on culturally sensitive English language teaching, offering practical guidance for curriculum designers, educators, and policymakers to enhance intercultural competence and contextual relevance in language learning.